Neo-liberalism masquerading as 'mixed economy'? a critical analysis of Namibia's principles of economic order (Journal for Studies in Humanities and Social Sciences, 2017)
Whereas a number of studies exists on the causes and impacts of inequality, poverty and unemployment, in which the majority of Namibians are trapped, very few, if any, of these studies cared to interrogate the role and place of the constitution in aiding the status quo. Most of the studies, even those on the constitu-tion, are often disinterested in the question of political economy, and how it relates to the constitution. A constitution can be understood as a set of fundamental laws determining the orientation (values and prin-ciples), structure and power of the state. To understand the economic system of a given state, the consti-tution ought to be the first point of call. In Namibia the picture is not as clear as it should be. The theory and the practice on the question of political economy do not necessarily intertwine. This text is concerned with the question of political economy. It analyses the constitutional principle of “Mixed Economy”, with the view to understand – and explain – the triumph of neoliberalism in Namibia. It impenitently concludes that, given the lack of clarity of the principle of “Mixed Economy” – a principle this text renders suspect – there is a need to relook at the constitution of the Republic of Namibia in order to address the question of political economy. The finding, however, is clear: Namibia is a neoliberal state.